2018
DOI: 10.1002/jsid.637
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient fluorescent blue materials and their applications for top‐emission OLEDs

Abstract: We developed new fluorescent blue dopants (BDs) for achieving high-efficient blue organic light-emitting diode. A new BD showed both high photoluminescent quantum yield >0.9 and highly horizontal orientation (S 0 > 0.9) in doped film with keeping a chemical stability by introducing suitable substituents. We developed hole transporting materials and optimized the combination of hole transporting layers to decrease a carrier accumulation at the interface between electron blocking layer and emission layer. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Figure 10 shows the BI of the tandem and single OLED devices as a function of the current density, respectively. The BI of the single OLED (D) shows over 200, which is extremely high value within the previous reports [11,14]. The high BI for the single OLED was attributed to both an intensity peak of relatively short wavelength and a narrow FWHM of a photo-luminescent spectrum.…”
Section: Blue Te Tandem Oled Devicesupporting
confidence: 82%
“…Figure 10 shows the BI of the tandem and single OLED devices as a function of the current density, respectively. The BI of the single OLED (D) shows over 200, which is extremely high value within the previous reports [11,14]. The high BI for the single OLED was attributed to both an intensity peak of relatively short wavelength and a narrow FWHM of a photo-luminescent spectrum.…”
Section: Blue Te Tandem Oled Devicesupporting
confidence: 82%
“…In order to enhance TTF efficiently, it is important to generate excitons locally to increase the exciton density. However, the previous studies have shown that excess carriers quench the localized triplet excitons and inhibit TTF 9,19 . It was also considered that locally increased high exciton density had an adverse effect on the device lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…However, the previous studies have shown that excess carriers quench the localized triplet excitons and inhibit TTF. 9,19 It was also considered that locally increased high exciton density had an adverse effect on the device lifetime.…”
Section: Concept Of Bilayer Emlmentioning
confidence: 99%
“…Replacing HT1 with another commercially available HT2, which is known to improve device lifetime in many occasions, in conjunction with our proprietary high-performance HBL materials (HB333), we constructed a second bottom-emission structure, Device Structure B: ITO/HT2:p-Dopant (100:3) (10 nm)/ HT (5 nm)/BH1:BD1 (100:5) (20 nm)/HB ET:LiQ (100:100) (25 nm)/Mg:Ag (100:10)(20 nm)/Ag (80 nm) found that the performance of ETL materials materials selection of another commercially which is known to improve device in conjunction with our performance HBL materials (HB333), emission device (10 nm)/ HT2 (100 nm)/B'1 HB333 (10 nm)/ 100:10)(20 nm)/Ag A closer look at the efficiency-luminance curve (Fig 2.) found that the efficiency at low luminance was improved for device with ET356 as ETL. This improvement of efficiency at low luminance is especially desirable for RGB side achieve high-quality gray scale [2] . Though ET201 could be a better choice than ET356 for customers adopting Device Structure A apparently better stability of the former customers adopting Device Structure B ET356 as their ETL materials.…”
Section: Resultsmentioning
confidence: 99%